Temperature effect on the static mode I delamination behavior of aerospace‐grade composite laminates: Experimental and numerical study. Issue 10 (11th July 2022) - Gong, Yu; Jiang, Linfei; Li, Linkang; Ren, Sue; Zhao, Youxuan; Wang, Ziming; Hu, Ning
Abstract: Aerospace structures are exposed to high‐temperature conditions during service. In‐depth study for the temperature effect on composite interlaminar properties is important for the structural design and reliable application. In this study, mode I delamination behaviors at different temperatures are investigated, to understand the effects of temperature on the delamination growth process, including fracture toughness, bridging stress, and failure mechanism. It is found that R ‐curve behavior presents at all temperatures. The initial and steady‐state fracture toughnesses exhibit linear increase trends with the increase of the temperature, from which equations are established to predict the initial and steady‐state fracture toughnesses at other temperatures. More bridging fibers are observed at higher temperatures, and the resulted fracture resistance at 130°C is 136.9% higher than that at room temperature. The maximum bridging stress also increases with the increase of temperature. A numerical framework based on the cohesive zone model is established for delamination modeling. Material parameters at various temperatures are obtained by an exponential model. Suitable values of interfacial parameters in cohesive elements are numerically determined. Predicted load–displacement responses agree well with the experimental ones, illustrating the applicability of the proposed numerical method. Highlights: Mode I delamination tests at various temperatures are performed on carbon/epoxy laminates. The initial and steady‐state fracture toughnesses exhibit a linear increase trend with the increase of the temperature. When temperature increases from 23°C to 130°C, the bridging fracture toughness and the maximum bridging stress have an increase of 136.9% and 150.1%, respectively. Numerical framework based on cohesive zone model is established for delamination modeling. Suitable values of interfacial parameters in cohesive elements are numerically determined.